A narrow-billed woodcreeper, lepidocolaptes angustirostris, nesting in a mailbox - Pizo, Marco A. [UNESP] (My University, 2018)
Documenting the adaptations of birds to live in urban areas is important in a context of an anthropogenically altered world where such areas may represent novel ecological opportunities for birds. Here I report on a nest of the Narrow-billed Woodcreeper Lepidocolaptes angustirostris in a wooden mailbox in a suburban area. The nest was found in the first week of November 2016 with three eggs, and later two nestlings that died within approximately one week likely due to water leaking into the box. The ability of L. angustirostris to use man-made structures for foraging and nesting, and its typical occurrence in open areas (thus differing from the family pattern of predominantly forest species) are factors permitting the occupation of urban habitats.
Keywords: Breeding biology; Dendrocolaptidae; Nest box; Suburban; Urban adapter